ABSORPTION CHARACTERISTICS OF THERMAL RADIATION FOR CARBON DIOXIDE - Jan Kubicki; Krzysztof Kopczyński; Jarosław Młyńczak (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The article presents graphs of absorption of thermal radiation as a function of the mass of absorbing carbon dioxide per unit of illuminated area. Experimental research was preceded by an analysis of a simplified model of radiation absorption, paying attention to the phenomenon of saturation. The results of the experimental research were compared with the theoretical ones and the discrepancies were interpreted. Based on the conclusions, suggestions were made regarding the impact of further CO2 emissions on climate change.